THE PENGARUH KUALITAS PELAYANAN KAPAL TERHADAP KEPUASAN PENGGUNA JASA PT PELABUHAN IDONESIA IV (PERSERO) CABANG MAKASSAR - Andi Rifka Darangeng; Najmi Kamariah (Jurnal Administrasi Negara, 2021)
State Owned Enterprise has the main task of providing economic services and goods that the private sector does not provide, as well as providing services related to all the needs and needs of the community. This study aims to explore further the effect of the quality of service provided by PT Pelabuhan Indonesia IV (Persero) Branch Makassar on the satisfaction felt by consumers. The sample in this study was obtained through non-probability sampling techniques and purposive sampling to take samples from research respondents. A total of thirty respondents were involved as samples in this study. The data processing model that will be carried out to analyze the results of this study is a simple regression analysis which is then processed by the SPSS application. Based on the results of the analysis of the coefficient of determination obtained from this study, the variable service quality has a 70.8% influence on the customer satisfaction variable. The results also show that customer satisfaction is positively and significantly affected (0.000 <0.05) by the quality of service provided by the company.